REVIEW OF THE FAST GROWING FOREST TREE SPECIES IN TURKEY - Ayan, Sezgin; Sıvacıoğlu, Ahmet (Comunicación invitada Boletín del CIDEU 2: 57-71 (2006), 2006)
The fast growing species have 50 year-old political and 35-40 year-old scientific background in Turkey. Eucalyptus camaldulensis Dehn., E. grandis W.Hill., Pinus pinaster Ait., P. radiata D. Don., hybrid poplars, some clones of Populus deltoides Bartr. ex Marsh. and P. nigra L. are the most important species for obtaining a great deal of progress in species and origin experiments and starting the plantation phase in Turkey. In fast growing species process; although the American species and origins are mostly used, the desired outcomes could not be achived because of establishing the experiments with few number of clones and origins, which didn’t represent the natural distribution area. Along with these species, studies should be focused on Pinus brutia Ten. which has broad natural distribution area in Turkey, improvement potential and fast growing character. Furthermore, P. brutia is evaluated as a species which will close the supply deficit in long run. Also, studies should be performed on Fraxinus angustifolia Wahl. subsp. oxycarpa Bieb ex Willd., Salix excelsa J. F. Gmelin., S. alba L., Pterocarya fraxinifolia Spach. and Alnus glutinosa Gaertn. subsp. barbata (C. A. Mey.) Yalt. which was experimented in regional base and showed the faster growing character than the other indigenous alder species and native species.
Keywords: Plantation, Industrial wood, Fast growing species, Origin, Indigenous